Characterization of modular bacteriophage endolysins from Myoviridae phages OBP, 201 phi 2-1 and PVP-SE1 - Walmagh, Maarten (2012)
Peptidoglycan lytic enzymes (endolysins) induce bacterial host cell lysis in the late phase of the lytic bacteriophage replication cycle. Endolysins OBPgp279 (from Pseudomonas fluorescens phage OBP), PVP-SE1gp146 (Salmonella enterica serovar Enteritidis phage PVP-SE1) and 201φ2-1gp229 (Pseudomonas chlororaphis phage 201φ2-1) all possess a modular structure with an N-terminal cell wall binding domain and a C-terminal catalytic domain, a unique property for endolysins with a Gram-negative background. All three modular endolysins showed strong muralytic activity on the peptidoglycan of a broad range of Gram-negative bacteria, partly due to the presence of the cell wall binding domain. In the case of PVP-SE1gp146, this domain shows a binding affinity for Salmonella peptidoglycan that falls within the range of typical cell adhesion molecules (Kaff = 1.26×106 M−1). Remarkably, PVP-SE1gp146 turns out to be thermoresistant up to temperatures of 90°C, making it a potential candidate as antibacterial component in hurdle technology for food preservation. OBPgp279, on the other hand, is suggested to intrinsically destabilize the outer membrane of Pseudomonas species, thereby gaining access to their peptidoglycan and exerts an antibacterial activity of 1 logarithmic unit reduction. Addition of 0.5 mM EDTA significantly increases the antibacterial activity of the three modular endolysins up to 2–3 logarithmic units reduction. This research work offers perspectives towards elucidation of the structural differences explaining the unique biochemical and antibacterial properties of OBPgp279, PVP-SE1gp146 and 201φ2-1gp229. Furthermore, these endolysins extensively enlarge the pool of potential antibacterial compounds used against multi-drug resistant Gram-negative bacterial infections.